Transformation of Green Open Space as a Source of Learning in Sustainable Environmental Development - Eko Adhy Setiawan (Civiliza Publishing, Indonesia., 2025)
Urban development is increasingly creating environmental pressures that threaten the ecological balance and quality of life in cities, particularly due to the decline of green open space (GOS) caused by rapid urbanization and land-use conversion. However, the historical transformation of green open space in the process of urban development has not been sufficiently studied from an integrative historical and analytical perspective. Therefore, this study aims to analyze the historical transformation of green open space in the context of sustainable urban environmental development. This study uses a qualitative approach with a historical-analytical design, utilizing data obtained from policy documents, urban planning archives, academic literature, and in-depth interviews with experts in the fields of urban planning and environmental management. The data are analyzed using an interactive qualitative analysis model involving data reduction, data display, and inference drawing to interpret patterns of transformation in the function, meaning, and governance of green open space across various periods of urban development. The results indicate that green open space has undergone a significant functional shift from traditional public-social space to strategic ecological infrastructure in sustainable urban planning. However, this study also finds a persistent gap between policy discourse promoting green open space and its practical implementation, largely due to land-use conflicts, economic development pressures, and institutional constraints. This study makes a theoretical contribution by emphasizing the importance of integrating historical perspectives into urban sustainability studies and offers insights for policymakers to strengthen environmentally oriented urban planning strategies.